تأثير بارامتر التوزع الاحتمالي الأسي لعدد الرزم على أداء شبكات MANET - محمد حجازية; بشار عباس (Tishreen University, 2018)
تحظى شبكات الـ MANET اليوم باهتمام العديد من الباحثين في مجالات الاتصالات والشبكات، نظراً لسهولة إنشاء مثل هذا النوع من الشبكات، وانتشارها الواسع في مختلف المجالات العلمية والتطبيقية، حيث عمد الباحثون إلى اقتراح العديد من بروتوكولات التوجيه في هذه الشبكات وما زالت عملية تطويرها جارية إلى يومنا هذا، حيث أن الهدف من عملية التطوير هو جعل هذه الشبكات أكثر أمنا واستقرارا بسبب أنها معرضة بشكل كبير للاختراق من قبل أي عقدة أخرى موجودة في محيط الشبكة نظراً لأن عوامل الأمان ضعيفة فيها. تم تصنيف هذه البروتوكولات حسب طريقة عملها إلى ثلاثة أصناف هي الصنف التفاعلي الذي يعتمد على إرسال رسائل تحكم عبر الشبكة من أجل تحديث المسارات التي تصل بين أي عقدتين فيها، والصنف الاستباقي الذي يعتمد على اكتشاف المسار عند الحاجة إليه فقط دون اللجوء إلى رسائل التحكم عبر الشبكة، والصنف الهجين الذي يجمع بين الصنفين السابقين فيقوم بتجزئة الشبكة إلى عناقيد حيث تتراسل العقد ضمن العنقود الواحد وفق الأسلوب التفاعلي بينما تتراسل العقد التي تتبع لعنقودين مختلفين وفق الصنف الاستباقي. تم في هذا البحث محاكاة شبكة الـ MANET من خلال إخضاع عملية توليد الرزم إلى توزع احتمالي أسي مع تغيير قيمة البارامتر 14(خ±)">  افتراضي من أجل الحصول على الأداء الأفضل عند تغير عدد العقد مع الأخذ بعين الاعتبار بارامترات المردود والحمل والتأخير الزمني. Today, MANET networks have attracted the attention of many researchers in the field of communications and networks because of the ease of establishing such networks and their wide spread in the various scientific and applied fields. The researchers have proposed many routing protocols in these networks. This is because the goal of the development process is to make these networks more secure and stable because they are highly vulnerable to penetration by any other node located in the perimeter of the network because the security factors are weak. These protocols are categorized according to its strategy to three types are the proactive class, which relies on the transmission of control messages over the network to update the routes between any two nodes, and the reactive class, which depends on discovering the route when needed, without broadcasting of control messages across network , And the hybrid type, which combines the two classes, that divides the network into clusters where the nodes interconnections within the cluster depends on the interactive method, while the transmission between two nodes that belong to different clusters is depend on proactive method. In this research, the MANET network was simulated by subjecting the packet generation process to an exponential probability distribution with the change of the value of the (α) parameter in order to obtain the best performance when the number of nodes changed taking into account the parameters of Throughput, load and delay.